Correlation Between Personal Hygiene Behavior During Menstruation and The Occurrence of Vulvar Pruritus at SMPN 1 Nassau - Lindawati Farida Tampubolon; Ice Septriani Saragih; Mei Misriani Hutapea; Elselina Saragih (Journal of Nursing Science Update (JNSU), 2023)
Vulvar Pruritus is a problem that often occurs during menstruation. This is a disorder of female external genitalia in the form of severe itching. This problem can be prevented through good personal hygiene behaviour. Personal hygiene is an action to maintain the health and hygiene of female organs during menstruation. This study aims to determine whether there is a relationship between personal hygiene behaviour during menstruation and vulvar pruritus in SMP Negeri 1 Nassau. This is correlation research with a cross-sectional design. Samples were female students at SMP Negeri 1 Nassau, with 102 respondents. The criteria of the sample are female students who have experienced menstruation. Female students who experience pruritus but not because of menstruation or are not in the vulvar pruritus category are excluded as a sample. The sample used a simple random sampling technique. Data were collected using a questionnaire and analyzed using the Pearson Product Moment test. The results showed that from 102 respondents, 86,3% had moderate behaviour doing personal hygiene. 51% of respondents had moderate vulvar pruritus, and only 11.8% had no problem. There was a weak correlation between female students' behaviour regarding personal hygiene during menstruation and pruritus vulva at SMP Negeri 1 Nassau with a result of p <0.05 (p=0.038). But even though it has a weak correlation, keeping personal hygiene of genital organs is very influential in reducing the risk of vulvar pruritus.